(3dOi CWaGd GdQhVI (BBullying (3HQfGeL bGFe Ydi bHYGJ GdJacjQ GdSJI ddMO ef GdJfeQ (B= s A program based on Six thinking hats to reduce bullying among Kindergarten children - (3fSQjf eMeO MGeOs; (3YdG MSf cGed (B: s; (3ceGd GdOjf MSjf eMeO (B: s; (3fhQgGf eMeO HgLJ CfhQ (B: s ((3GdbGgQI (B: s (3fSQjf eMeO MGeO (B: s, 2021)
(3JgOa GdOQGSI GdMGdjI Edi ESJNOGe ESJQGJjLjI bHYGJ GdJacjQ GdSJI ddMO ef GdJfeQ eY CWaGd GdQhVI h ESJNOeJ GdHGMKI GdefgL GdhUai h GdefgL GdJLQjHi(B: (3h ETJedJ YjfI GdOQGSI fMh (B60 (3Wad h WadI JJQGhM CYeGQge eG Hjf (B5-6 (3SfhGJ ef QhVI eOQSI CfLdh CeQjcGf ddZGJ(B: (3h bO ESJNOeJ GdHGMKI ENJHGQ (B- (3GdeUahaGJ GdeJJGHYI GdedhfI d QGaf (B((3JYOjd h Jbfjf(B) / (3YeGO CMeO MSf h ebjGS eUhQ ddJMUjd (B((3EYOGO GdHGMKI(B) (3h HQfGeL CfTWI eJfhYI (B((3EYOGO GdHGMKI(B): (3h bO JhUdJ GdOQGSI GdMGdjI Edi hLhO aQhb PGJ OdGdI EMUGFjI Hjf eJhSWj OQLGJ CWaGd GdeLehYI GdJLQjHjI h CWaGd GdeLehYI GdVGHWI ai GdbjGS GdHYOi dJWHjb GdHQfGeL GdbGFe Ydi bHYGJ GdJacjQ GdSJI Ydi GdebjGS GdeUhQ ddMO ef GdJfeQ dUGdM GdeLehYI GdJLQjHjI(B: (3h hLhO aQhb PGJ OdGdI EMUGFjI Hjf eJhSWI OQLGJ GdeLehYI GdJLQjHjI ai GdbjGSjf GdbHdi h GdHYOi dJWHjb GdHQfGeL GdbGFe Ydi bHYGJ GdJacjQ GdSJI Ydi GdebjGS GdeUhQ ddMO ef GdJfeQ dUGdM GdbjGS GdHYOis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI ddWahdI GdeHcQI (B- (3bSe GdYdhe GdCSGSjI s
(3UOQ GjVG cbQU eOeLs
Keywords: (3CWaGd GdQhVIs; (3GdJfeQs; (3bHYGJ GdJacjQ GdSJIs